Exploring Islamic education teachers' competency in teaching tilawah al-Quran in two selected secondary schools in Gombak : a case study - Azila binti Rafee (Kulliyyah of Education , International Islamic University Malaysia, 2014)
Tilawah al-Quran is one of the components of the Islamic Education curriculum of primary and secondary schools in Malaysia. Teaching Tilawah al-Quran involves verbal skills, reading fluency, skills of fasohah, recitations with tajweed and reading with tadwir and tartil, and comprehension of Quranic verses. Successful outcome of teaching and learning Tilawah al-Quran requires skilled and competent teachers. These requirements are vital for Islamic Education teacher so that they can master the teaching of Tilawah al-Quran effectively. Thus, this study attempts to explore Islamic Education teachers' competency in teaching Tilawah al-Quran. This study employed a case study approach. Data were collected through interviews and classroom observations. This study was carried out in two Malaysian secondary schools in Gombak district. The study was involved three Islamic Education teachers. The study found that in order to be competent in teaching Tilawah al-Quran, teacher should have knowledge, appropriate skills and teaching methods. The data analysis revealed that the five elements of teaching competencies applied by the Islamic Education teachers in teaching Tilawah al-Quran include teaching methodology, using teaching aids, using classroom management techniques, assessing and evaluating students learning, and possessing good personality and attitude. The study suggested that to become a competent teacher in teaching Tilawah al-Quran, an Islamic Education teacher should be knowledgeable, having teaching skills especially the ability to teach and transmit the knowledge and skills to students, as well as using appropriate pedagogies. Additionally, Islamic Education teacher should have good personality and attitude.